ANALISIS IMPLEMENTASI KURIKULUM MERDEKA PADA PEMBELAJARAN BERDIFERENSIASI DI SMP NEGERI 7 ARUT SELATAN - saraswati, dwi (JURNAL KEBIJAKAN PUBLIK, 2025)
The background of this research is to determine the effectiveness of differentiated learning implemented by teachers due to the different abilities of students in the process of absorbing knowledge. The current curriculum, namely the Merdeka Belajar Curriculum, provides a container and emphasizes the freedom of students to determine the course of learning according to their interests, needs, and potential. However, it is necessary to recognize that each student has a different level of understanding and ability in studying subjects in school. This research aimed to analyze the implementation of differentiated learning in SMP Negeri 7 Arut Selatan. This research is important to validate the effectiveness of implementing the independent curriculum through differentiated learning processes. The research method used is quantitative with a descriptive statistical approach. Research data is obtained from the results of questionnaires, learning outcomes data and interview which are described descriptively. The research results showed that the Merdeka Curriculum which has been implemented in SMP Negeri 7 Arut Selatan, Kotawaringin Barat since the 2023-2024 school year with the implementation of a differentiated approach has been running very effectively. These results showed that SMP Negeri 7 Arut Selatan can be a role model in implementing the Merdeka Curriculum for other schools.